Buybust [videorecording (DVD)] - Matti, Erik; Matti, Erik; Matti, Erik; Curtis, Anne, 1985-; Vera, Brandon; Neri, Victor (Well Go USA Entertainment, 2018)
Narcotics officer Nina Manigan and her team become trapped between a drug gang and angry civilians after a mission goes wrong.